Pembayaran Zakat Non-Tunai Secara Online dalam Perspektif Hukum Islam - Haliza Nur Madhani; Herlina Herlina; Radiatul Hafifah; Radiatus Sholehah; Ali Murtadho Emzaed (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
Along with the rapid advancement of digital technology, the practice of zakat payment has also evolved, such as by making non-cash zakat payments online. Online zakat payment offers the potential to reach zakat givers and recipients more broadly, as well as to increase efficiency in the collection and distribution of zakat funds through a digital system. However, this online zakat payment system still raises debates among the public regarding the validity of its implementation and the law, which is considered unclear because the method was not found in the time of the Prophet Muhammad SAW. Therefore, this research was conducted to examine the concept, Islamic legal review, advantages and disadvantages, as well as challenges and solutions in the application of the online non-cash zakat payment system from the perspective of Islamic law. This research uses normative legal methods in qualitative form and by conducting a literature study of literature or library materials. The findings of this research show that online non-cash zakat payments are sharia-acceptable as long as they fulfill the pillars and conditions of zakat and are carried out by official amil zakat institutions or platforms affiliated with amil zakat institutions.